Laminin and fibronectin in adenoid cystic carcinoma. - d'Ardenne, A J (J Clin Pathol, 1986)
The distribution of fibronectin and laminin was examined by immunohistochemistry in 11 adenoid cystic breast carcinomas, six adenoid cystic carcinomas of mouth and salivary gland, and six cribriform ductal breast carcinomas. Both proteins were present lining cystic lumina and around tumour islands in all the adenoid cystic breast carcinomas and in five of six salivary gland tumours. Abundant laminin and fibronectin were dispersed among adenoid cystic tumour cells arranged in sheets. One adenoid cystic carcinoma from buccal mucosa showed a transition from a cribriform tumour positive for both fibronectin and laminin to a cribriform tumour negative for fibronectin and laminin to undifferentiated carcinoma. Fibronectin and laminin seemed to disappear simultaneously from tumour cell surfaces. Another adenoid cystic carcinoma from buccal mucosa was negative for fibronectin and laminin from the time of initial biopsy. This was the only tumour that gave rise to disseminated metastases, resulting in the death of the patient within two years of surgery. In cribriform invasive ductal breast carcinomas the linings of cystic lumina were always negative for fibronectin and laminin. Varying quantities were present at the tumour boundaries. We suggest that staining for fibronectin and laminin may be a valuable aid to the diagnosis of adenoid cystic carcinomas and that the absence of these proteins may have important prognostic implications. IMAGES: